Pontine and cerebellar injury in neonatal hypoxic-ischemic encephalopathy: MRI features and clinical outcomes. (October 2020) - Hayakawa, Katsumi; Tanda, Koichi; Koshino, Sachiko; Nishimura, Akira; Kizaki, Zenro; Ohno, Koji
Background: Perinatal hypoxic-ischemic encephalopathy (HIE) is a major cause of death and disability in infants. Magnetic resonance imaging (MRI) is valuable for predicting the outcome in high-risk neonates. The relationship of pontine and cerebellar injury to outcome has not been explored sufficiently. Purpose: To characterize MRI features of pontine and cerebellar injury and to assess the clinical outcomes of these neonates. Material and Methods: The retrospective study included 59 term neonates (25 girls) examined by MRI using 1.5-T scanner in the first two weeks of life between 2008 and 2017. Involvement of the pons and cerebellum was judged as a high signal intensity on diffusion-weighted image (DWI) and a restricted diffusion on an apparent diffusion coefficient (ADC) map. Results: Pontine involvement was observed in the dorsal portion of pons in eight neonates and cerebellar involvement was observed in dentate nucleus (n = 8), cerebellar vermis (n = 3), and hemisphere (n = 1) in 11 neonates. Combined pontine and cerebellar involvement was observed in eight neonates and only cerebellar involvement in three. The pontine and cerebellar injuries were always associated with very severe brain injury including a basal ganglia/thalamus injury pattern and a total brain injury pattern. In terms of clinical outcome, all but four lost to follow-up, had severe cerebral palsy. Conclusion: Pontine and cerebellar involvement occurred in the dorsal portion of pons and mostly dentate nucleus and was always associated with a more severe brain injury pattern as well as being predictive of major disability.